2020
DOI: 10.1186/s13550-020-00651-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-to-liver ratio determined by [68Ga]Ga-DOTA-TOC PET/CT as a prognostic factor of lanreotide efficacy for patients with well-differentiated gastroenteropancreatic-neuroendocrine tumours

Abstract: Background: Lanreotide is a long-acting somatostatin analogue with proven antitumour effects against well-differentiated (WD) gastroenteropancreatic-neuroendocrine tumours (GEP-NETs). However, there are no globally established prognostic factors associated with the efficacy of lanreotide as a treatment for GEP-NETs. We investigated the prognostic value of [ 68 Ga]Ga-DOTA-TOC positron emission tomography (PET)/computed tomography (CT) somatostatin receptor imaging for patients with WD GEP-NETs treated with lanr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 32 publications
(39 reference statements)
4
45
0
Order By: Relevance
“…In this study, correlation analysis between nuclear imaging findings and efficacy outcomes was not preplanned. Considering the potential relevance of nuclear imaging in predicting the prognosis of patients with GEP-NETs, 19 post hoc analysis was carried out for patients who underwent nuclear imaging (Gallium 68-DOTATOC [ 68 Ga-DOTATOC] and/or 18F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) before treatment. Briefly, 68 Ga-DOTATOC and 18 F-FDG PET/CT images from the vertex to the upper thigh were acquired approximately 60 min after intravenous administration of 68 Ga-DOTATOC 148 MBq (4 mCi) and 18 F-FDG 0.14 mCi/kg, respectively (GE Discovery PET/CT 690, 690 Elite, or 710; GE Medical Systems, Milwaukee, WI).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, correlation analysis between nuclear imaging findings and efficacy outcomes was not preplanned. Considering the potential relevance of nuclear imaging in predicting the prognosis of patients with GEP-NETs, 19 post hoc analysis was carried out for patients who underwent nuclear imaging (Gallium 68-DOTATOC [ 68 Ga-DOTATOC] and/or 18F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) before treatment. Briefly, 68 Ga-DOTATOC and 18 F-FDG PET/CT images from the vertex to the upper thigh were acquired approximately 60 min after intravenous administration of 68 Ga-DOTATOC 148 MBq (4 mCi) and 18 F-FDG 0.14 mCi/kg, respectively (GE Discovery PET/CT 690, 690 Elite, or 710; GE Medical Systems, Milwaukee, WI).…”
Section: Methodsmentioning
confidence: 99%
“…Second, [ 68 Ga]Ga-DOTA peptide uptake can have prognostic value. Low uptake has been shown to be an indicator of poor prognosis in adults with neuroendocrine tumors [92][93][94], but this has not been studied in neuroblastoma. Nevertheless, higher SSTR2 expression is correlated with higher [ 68 Ga]Ga-DOTATATE uptake [94].…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…Other systemic therapeutic options such as targeted therapy or cytotoxic chemotherapy could be used for patients with a high Ki-67 index or high tumor volumes, but SSAs should not be precluded in these cases given their favorable toxicity profiles. 68 Ga-based SSTR targeting PET/CT may be helpful in predicting the efficacy outcomes of SSA treatments [16,20] 8 Korean Cancer Association This article is protected by copyright. All rights reserved.…”
Section: Somatostatin Analoguesmentioning
confidence: 99%
“…Previous studies have shown that these gallium-based functional imaging methods are sensitive and deliver complementary information that is very useful for therapeutic decision-making [ 20 , 22 ]. 68 Ga-DOTA-TOC positron emission tomography (PET)/CT is available for use in Korea but is not currently reimbursed by the national health insurance system [ 23 ].…”
Section: Diagnostic Work-upsmentioning
confidence: 99%